Cannibalistic Caterpillars (Utetheisa ornatrix; Lepidoptera: Arctiidae) Fail to Differentiate between Eggs on the Basis of Kinship - James F. Hare; Thomas Eisner (Psyche: A Journal of Entomology)
Utetheisa ornatrix larvae, in exercising egg cannibalism, do not discriminate between kin and nonkin. Under natural conditions this may not be a handicap, partly because the larvae hatch largely in synchrony and do not immediately upon emergence engage in cannibalism.